Antibiotic associated diarrhoea in paediatric outpatient practice - Anumolu, Srimukhi; Edagotti, Gowri; Rahman, M. A. (International Journal of Contemporary Pediatrics, 2021)
Background: To document the profile of antibiotic associated diarrhoea (AAD) in children aged 6 months to 15 years receiving oral antibiotics. Methods: Prospective study of children attending the out-patient department, who were started on oral antibiotic for indications other than gastrointestinal infections. Data collection was done with a questionnaire and follow up was done by telephone. Results: Of the 1022 children, seven developed AAD (0.68%). Twenty-nine other children had loose stools but did not fulfil the criteria of AAD. Of 436 children who received Amoxicillin clavulanate, 4 developed AAD. One each from 361 on amoxicillin, 9 on ciprofloxacin and 8 on erythromycin developed AAD. Five of the seven children who had diarrhoea were less than two years (71.4%). Conclusions: Incidence of AAD is very low in an out-patient setting. In all cases, diarrhoea subsided on stopping the antibiotic. Children below two years of age and those on Amoxicillin clavulanate have a significantly higher risk.